From "helping peers succeed" to "struggling to develop research questions": factors that contribute to and detract from science identity in undergraduate learning assistants - Lilian J. Baker; Zoe K. Abel; Cynthia J. Brame (Springer, 2024)
Abstract Science identity impacts undergraduates' persistence in their science courses and careers. Here, we investigated science identity in learning assistants, undergraduate peer educators who provide academic and social support in science courses. Understanding learning assistants' science identities has particular value because of their dual role as science students and peer educators. While previous research has investigated disciplinary identity among physics learning assistants, we extend that work by investigating science identity among students who served as learning assistants in six different science courses, seeking to understand the ways in which they characterize their science identity and the experiences they describe as important in its development. Analysis of twelve interviews revealed three distinct groups of learning assistants: those with lower, intermediate, and high science identities. Recognition by important others, research experiences, and constrictive definitions of science were salient for science identity across all groups, while other experiences had varied salience. Notably, learning assistants with lower science identity described learning to use scientific language as critical for identity development, while learning assistants with the highest science identity found helping others to be an important contributor. Surprisingly, learning assistants with intermediate science identity cited uncertainty about their ability to develop research projects as important for determining their science identity. To communicate the variation in and factors relevant to science identity among learning assistants, we have developed three personas that can serve as tools to help programs and instructors develop robust support for learning assistants' science identity.